(untitled) (Vietnam Journal of Community Medicine, 2021)
Central-line associated bloodstream infection (CLABSI) is a common condition in health care with serious consequences. Objective: To determine the CLABSI incidence rate at the Vietnam National Children’s Hospital, in 2020 and some factors related to CLABSI status. Methods: A cross-sectional descriptive study was conducted in 5 departments in Vietnam National Children’s Hospital from January 2020 to June 2020. The study included 602 pediatric patients who inserted a central catheter after hospitalization. Results: The incidence rate of CLABSI in the study was 4.0 per 1000 days - catheter. This rate is highest in the Emergency department of neonatal, at 6.3 per 1000 days - catheter. The risk of CLABSI is higher in infants than in older children, and it is regardless of gender. The risk of CLABSI in the Viet Nam National Children’s Hospital is higher in the Emergency department of neonatal than in other departments, in children with neonatal contraceptives in umbilical vein, with a retention time of 7 days or more. The risk of CLABSI is reduced in cases where proper hand hygiene is performed; this risk is also reduced in cases of properly disinfected. Conclusion: The incidence of CLABSI in the study was quite low. The risk of developing CLABSI is related to age group, catheterization department, location of the contraceptive device, the length of time it is stored, and the compliance with proper antiseptic and hand hygiene measures.